Similar magnitude of post-exercise hyperglycemia despite manipulating resistance exercise intensity in type 1 diabetes individuals - Steve Luzio (Scandinavian Journal of Medicine & Science in Sports, 2016)
The aim of this study was to compare the glycemic and glucoregulatory hormone responses to low‐ and moderate‐intensity morning resistance exercise (RE ) sessions in type 1 diabetes (T1DM ). Following maximal strength assessments (1RM ), eight T1DM (HbA 1C:72 ± 12 mmol/mol, age:34 ± 7 years, body mass index:25.7 ± 1.6 kg/m2) participants attended the research facility on two separate occasions, having fasted and taken their usual basal insulin but omitting rapid‐acting insulin. Participants performed six exercises for two sets of 20 repetitions at 30%1RM during one session [low‐intensity RE session (LOW )] and two sets of 10 repetitions at 60%1RM during another session [moderate‐intensity RE session (MOD )], followed by 65‐min recovery. Sessions were matched for total mass lifted (kg). Venous blood samples were taken before and after exercise. Data (mean ± SEM ) were analyzed using analysis of variance (P  ≤ 0.05). There were no hypoglycemic occurrences throughout the study. Blood glucose rose similarly between sessions during exercise (P  = 0.382), remaining comparable between sessions throughout recovery (P  > 0.05). There was no effect of RE intensity on metabolic acidosis (P  > 0.05) or peak growth hormone responses (P  = 0.644), but a tendency for greater catecholamine responses under LOW (individualized peak concentrations: adrenaline MOD 0.55 ± 0.13 vs LOW 1.04 ± 0.37 nmol/L , P  = 0.155; noradrenaline MOD 4.59 ± 0.86 vs LOW 7.11 ± 1.82 nmol/L , P = 0.082 ). The magnitude of post‐exercise hyperglycemia does not differ between equal volume low and moderate intensity RE sessions performed in the morning.